TOURISM INDUSTRY OF JAMMU & KASHMIR – CHALLENGES AND OPPORTUNITIES - Shabir Ahmad Lone; Dr. E.Ravi (CV. Radja Publika, 2023)
ABSTRACT Almost every economy in the world relies on tourism to generate cash, create job opportunities, and contribute to the economy's GDP. Tourism is also playing a significant role in the overall development of the state's economy in Jammu and Kashmir. Kashmir has been aptly termed as